‘Trustworthy Allies’: International Organisations, Ernest Hemingway, Women Activists, and Spanish Republican Exiles in Cuba - Daniel Fernandez Guevara (Culture & History Digital Journal)
A shortage of scholarship exists on US private chartable aid organisations and their efforts to help exiles of the Spanish Civil War. Notably, if the literature on US private aid groups is scant for the Spanish conflict, the research is simply non-existent for refugees who made their way to Cuba or the women in the United States who facilitated aid for these refugees. Thus, this essay addresses a crucial lacuna in the historiography by examining how US aid groups dealt with the crisis on the island. Buoyed by files in the American Friends Service Committee archive and my research in Cuba, I reveal that the confluence of Cuban state hostility against Spanish exile settlement, US private aid´s penchant for advancing a ‘national’ image abroad, and the author Ernest Hemingway´s close relationships to the ‘loyalist’ cause and its exiles, resulted in a selective distribution of aid by mostly women at ‘neutral’ private aid organisations.